Muslim Influencers and Moral Responsibility: An Ethical Analysis of Preaching on Digital Platforms - Najamudin Najamudin; Dwi Muliati; Amelia Agustin; Mansur Tenis (LP3M Pascasarjana STAI Ibnurusyd, 2026)
The development of digital media has given rise to a new phenomenon in dawah, namely the emergence of Muslim Influencers. This study aims to analyze the moral and ethical responsibilities of dawah that should be upheld by Muslim Influencers on digital platforms. The method used is qualitative with a library research approach, with data collected from various literature sources such as journals, books, and related academic works. The results of the study indicate that although the term